TCP15 interacts with GOLDEN2-LIKE 1 to control cotyledon opening in Arabidopsis - Alem, Antonela Lucía (2022)
After germination, exposure to light promotes the opening and expansion of the cotyledons and the development of the photosynthetic apparatus in a process called de-etiolation. This process is crucial for seedling establishment and photoautotrophic growth. TEOSINTE BRANCHED 1, CYCLOIDEA, and PROLIFERATING CELL FACTORS (TCP) transcription factors are important developmental regulators of plant responses to internal and external signals that are grouped into two main classes. In this study, we identified GOLDEN2-LIKE 1 (GLK1), a key transcriptional regulator of photomorphogenesis, as a protein partner of class I TCPs during light-induced cotyledon opening and expansion in Arabidopsis. The class I TCP TCP15 and GLK1 are mutually required for cotyledon opening and the induction of SAUR and EXPANSIN genes, involved in cell expansion. TCP15 also participates in the expression of photosynthesis-associated genes regulated by GLK1, like LHCB1.4 and LHCB2.2. Furthermore, GLK1 and TCP15 bind to the same promoter regions of different target genes containing either GLK or TCP binding motifs and binding of TCP15 is affected in a GLK1-deficient background, suggesting that a complex between TCP15 and GLK1 participates in the induction of these genes. We postulate that GLK1 helps to recruit TCP15 for the modulation of cell expansion genes in cotyledons and that the functional interaction between these transcription factors may serve to coordinate the expression of cell expansion genes with that of genes involved in the development of the photosynthetic apparatus.